PENERAPAN MEDIA AUDIO VISUAL PADA GURU SMA BAKTI IDHATA DALAM PEMBELAJARAN JARAK JAUH - Novrita Mulya Rosa; Ahmad Suryadi; Robiatul Adawiyah (Abdi Jurnal Publikasi, 2023)
This community service program aims to provide training on the application of audio-visual media to Bakti Idhata High School teachers in distance learning as an effort to increase teacher competence in utilizing technology and audio-visual media in distance learning. This program uses a competency-based training approach with training methods consisting of concept introduction, practical training, and evaluation stages. The training participants consisted of 15 Bakti Idhata High School teachers who had experience in distance learning. The results of the community service program show that training in the application of audio-visual media to Bakti Idhata High School teachers in distance learning can increase teacher competence in utilizing technology and audio-visual media in distance learning. Teachers participating in this program reported that they had a better understanding of the use of audio-visual media in distance learning and were able to apply the concept in their teaching practice. The program also provides significant benefits for students. Students reported that they were more interested and easy to understand learning material when it was delivered using audio-visual media. This community service program indicates that training in the application of audio-visual media to Bakti Idhata High School teachers in distance learning can provide significant benefits for teachers and students. Therefore, it is advisable for educational institutions and the government to adopt a training program for implementing audio-visual media for high school teachers in distance learning as an effort to improve the quality of learning in the future. Keywords : audio visual media, distance learning, training, high school teachers, teacher competence, technology